PENGARUH E-WORD OF MOUTH, DISKON, DAN ALGORITMA TERHADAP KEPUTUSAN PEMBELIAN DI TIKTOK SHOP MASYARAKAT GEN-Z KOTA MEDAN - Aaron Wilson; Yeni Rafita Sihombing; Christopher Christopher; Vincent Tofansza (Journal of Economic, Bussines and Accounting (COSTING), 2026)
The development of digital technology has changed consumer behavior, especially Generation Z who actively use social media such as TikTok. Through the TikTok Shop feature, users can shop directly within the application supported by video content and a personalized algorithm system. This study aims to determine the influence of e-word of mouth, discounts, and algorithms on the purchase decisions of Gen-Z consumers in Medan City.This study uses a quantitative approach with a causal research design. The population in this study consists of Gen-Z individuals in Medan City who are active users of TikTok Shop, with a sample of 97 respondents determined using the Lemeshow formula. Data collection techniques were conducted using questionnaires with a Likert scale, and data analysis was performed using multiple linear regression through SPSS. The results show that partially the variables of e-word of mouth, discounts, and algorithms have a positive and significant influence on purchase decisions. Simultaneously, these three variables also have a positive and significant influence on purchase decisions with a coefficient of determination (Adjusted R²) value of 0.798. This means that 79.8% of purchase decisions are explained by these three variables, while 20.2% are influenced by other factors such as influencer marketing, live streaming, and product quality. These findings confirm that positive reviews, discount strategies, and TikTok's algorithm system that displays content according to user preferences play an important role in encouraging consumer behavior and purchase decisions among Gen-Z consumers in Medan City.